PELAKSANAAN PEKERJAAN PLAT LANTAI DENGAN BETON PRECAST PADA PROYEK PENATAAN GGM TAHAP 1 - Depi Nur Pajriah (Universitas Majalengka, 2022)
Abstract The building structure is one of the most important elements in a building construction. So the selection of the right implementation method is very important to be able to get the best and maximum results. Replacing conventional methods to become more modern is one of the efforts that can be done by managers. As in the implementation of the skywalk work, it also uses a more modern method, namely by applying a precast concrete system to the floor slab. The purpose of this study: (1) to know and understand how to carry out the work of preparing/installing precast concrete floor slabs. (2) knowing and understanding how to carry out precast concrete connection work. From this it will be known the method of implementation, the stages of implementation carried out, the specifications of the precast concrete used, as well as the types and specifications of the heavy equipment used.The results of this study are: the implementation stage starting from the mobilization of materials, preparation work, HCS work and the last stage is the connection stage. The precast used are: Width 1,200 mm, Length 3,720 mm, Weight 932.14 kg. The iron used in the connection is D10 in size. Keywords: Precast concrete, Implementation Method, floor slab